Initial Inventory of Plastics Imports in Nigeria as a Basis for More Sustainable Management Policies - Babayemi, Joshua O. (J Health Pollut, 2018)
BACKGROUND. Plastic is a waste stream with recycling and recovery potential. However, the recycling rates for plastic in African countries are low. Furthermore, use and production of virgin plastics are increasing. Therefore, a high proportion of plastic waste is being disposed of in landfills and dumpsites. Plastic serves as fuel for open burning at landfills/dumpsites with associated releases and constitutes a large fraction of marine litter, making it a major and growing global pollution concern. OBJECTIVES. This study aims to develop an initial inventory of plastics in Nigeria towards the development of an effective plastics management frame. METHODS. A search was conducted of the recent literature and the United Nations (UN) Comtrade database using harmonized system (HS) codes for import data of various polymer categories and major product categories containing plastic. Algebraic expressions were developed for calculation of the share of plastic in these products. RESULTS. Approximately 14,200,000 tons of plastics in primary form were imported into Nigeria between 1996–2014. Approximately 3,420,000 tons total plastic were imported in the form of products and approximately 5,545,700 tons were imported as product components. Approximately 194,000 tons of plastic toys were imported over a six-year period. DISCUSSION. The total amount of plastics imported in primary form and as products equals 17,620,000 tons. The total volume of imported plastic, newly produced plastic and plastic components going into the technosphere was 23,400,000 tons. The huge amount of plastic and other polymers entering the technosphere in Nigeria has important implications for marine litter, pollution, waste management and resource recovery. CONCLUSIONS. A huge volume of plastics has entered the Nigerian technosphere, with less than 12% of the resulting waste entering the recycling stream. There is a need for sustainable management of this crucial waste and resource category. Potential mitigating strategies include waste plastic reuse, recycling, waste conversion to energy, and appropriate plastic control policy frameworks. COMPETING INTERESTS. The authors declare no competing financial interests.